Implementation of the "sponge city" development plan in China: An evaluation of public willingness to pay for the life-cycle maintenance of its facilities. (October 2019) - Ding, Lei; Ren, Xiangyu; Gu, Runzhu; Che, Yue
Abstract: Urban stream syndrome, including urban waterlogging, flood risk, water shortage, water pollution and ecological restoration, are major challenges that cause potential risks to human beings. Recently, the sponge city construction (SCC) initiative in China has received extensive attention because it aims to systematically solve all of these urban water-related issues for a city. To date, little research has focused on the life-cycle operations, maintenance requirements and low public awareness of sponge city facilities (SCFs; e.g., rain gardens, green roofs, grass swales, and pavement greenbelts), which are challenges facing the development and sustainability of the SCC initiative. The aim of this study is to explore (i) the willingness to pay (WTP) for the life-cycle maintenance of SCFs and its determinants and (ii) the public's perceptions and attitudes towards the SCC initiative. We conducted a questionnaire-based survey combined with contingent valuation in three pilot sponge cities and then applied a two-phase logistic model and Tobit model to estimate the WTP of the respondents and the factors influencing the WTP. The results show that 76% of the respondents agreed to pay for life-cycle maintenance of SCFs, and the median amount of WTP was 16.57 CNY (2.53 USD) per month. Important factors influencing WTP include respondents' perceptions of the efficacy of the SCFs, concerns regarding the waterlogging risk and support for the SCF construction plans. The findings of this research extend our knowledge of the public's perceptions of and attitudes towards the SCC initiative and suggest that public contributions could serve as a crucial and feasible funding source for the life-cycle maintenance of SCFs. Highlights: WTP for life-cycle maintenance of the sponge city facilities were evaluated. A two-phased system of logistic and Tobit model analyses was applied for the empirical study. The estimate median WTP for the sponge city facilities was 16.57 CNY. Key significant influencing factors were identified. Policy recommendations on sponge city development were proposed.